Clinical Use of Propranolol Reduces Biomarkers of Proliferation in Gastric Cancer - Hu, Qian; Liao, Ping; Li, Wei; Hu, Jiali; Chen, Cuiyu; Zhang, Yu; Wang, Yang; Chen, Ling; Song, Kun; Liu, Jie; Zhang, Wei; Li, Qing; et al. (Frontiers in Oncology, 2021)
Gastric cancer has one of the highest mortality rate in the world, but the treatment is still limited. Building on previous studies, mechanistic studies on propranolol in gastric cancer mice models and gastric cancer patients were performed. Propranolol inhibited the in vitro proliferation of gastric cancer cells in a time and concentration dependent manner. Western blot analysis proved that propranolol can decrease the expression of AKT/MAPK signaling pathway-related proteins. Consistent findings were observed in MFC tumors engrafted 615 mice, which were treated with propranolol at 10 mg/kg daily for 14 days. Propranolol inhibited the phosphorylation of AKT, MEK, and ERK proteins than control in mice tumor tissues respectively (p-AKT 26.16 vs. 56.82, P=0.0196, p-MEK 28.27 vs. 59.28, P=0.1102, p-ERK 48.2 vs. 107.4, P=0.0062). Propranolol had antiproliferative activity in gastric cancer patients receiving 60 mg daily for 7 days prior to surgery(ki67 44.8 vs 125.3 for placebo; p=0.02). Phosphorylated AKT, MEK, and ERK did not differ between propranolol and placebo treatment in gastric cancer patients. The expression of molecules on CD8+ T cells were not changed both in mice model and patients. Nor was there a statistically significant difference in CD8+ T cell subsets in patients, although suggestion of an effect was evident. These results prove that propranolol may inhibit the growth of gastric cancer in mice model and patients and the possible mechanism was via inhibiting the AKT and MAPK pathways, but the frequency of tumor infiltration CD8+ T cells didn’t increase significantly.